Causality Between ICT, Financial Development And Economic Growth In Kenya - Musakwa Mercy T.; Odhiambo Nicholas M. (Folia Oeconomica Stetinensia)
The growing importance of information and communication technology (ICT) in every facet of life motivated this study to examine the association between ICT, financial development and economic growth.